Decomposing Difficulty of Reading Literacy Test Items - Алина Иванова; Инна Антипкина (Вопросы образования, 2023)
The current study investigates the question of test difficulty decomposition depending on the characteristics of items (such as: format, belonging to the type of text to which the item belongs) and the reader's actions required to answer it (search for information in the text, simple conclusions, complex conclusions, critical interpretation of the text). The sample of the study consisted of fourth grade elementary school students in Krasnoyarsk, who completed the computerized test of reading literacy "Progress" in the spring of 2022. Research method: psychometric modeling using the LLTM+e model. Research hypothesis: the decomposition of item difficulties will help to prove that the reading actions required to complete the tasks will form a hierarchy of difficulties similar to traditional taxonomies (B. Bloom), that is, reading skills aimed at analyzing, synthesizing, interpreting information will give tasks greater difficulty than simple conclusions, and those, in turn, will make tasks more difficult than the reader's actions to find information in the text. The results show that the assignment of items to the group of reader's actions is a significant factor. The size of the effects does not allow us to speak of a strict hierarchy, but when other attributes are controlled, the tasks for information retrieval in an explicit form are easier for students than the tasks for complex conclusions and for critical understanding of the text.